2010
DOI: 10.1111/j.1439-0396.2009.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient digestibility, but not mineral absorption, is age-dependent in cats

Abstract: Availability of nutrients is influenced by extremes of age, and a better characterization of this influence is necessary for appropriate development of foods and nutritional management throughout life stages of cats. This study investigated nutrient digestibility, mineral absorption, faeces and urine production in three groups of six young, mature and old cats fed two diets containing different energy densities. Apparent digestibility and mineral absorption were calculated by total collection method and values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 22 publications
3
22
0
1
Order By: Relevance
“…In this study, old cats showed a marked reduction in the digestibility of dry matter, protein, and energy, consistent with results from other studies (Taylor et al., 1995; Peachey et al., 1999a; Teshima et al., 2010). A reduction in energy digestibility in older cats may partly explain the larger energy intake and expenditure (Harper, 1998).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, old cats showed a marked reduction in the digestibility of dry matter, protein, and energy, consistent with results from other studies (Taylor et al., 1995; Peachey et al., 1999a; Teshima et al., 2010). A reduction in energy digestibility in older cats may partly explain the larger energy intake and expenditure (Harper, 1998).…”
Section: Discussionsupporting
confidence: 93%
“…The reasons for reductions in nutrient digestibility are, however, unclear. Intestinal transit time appears to be unaffected by age (Peachey et al., 2000), although older cats appear to have increased variation in both nutrient digestibility and transit time compared with younger cats (Peachey et al., 2000; Teshima et al., 2010). In the current study, the coefficient of variation for dry matter, protein and energy digestibility in young and old cats was similar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, Teshima et al. () reported sodium digestibilities of 78% in low‐energy diets (13.7 MJ ME/kg) and 89.5% in high‐energy diets (16.8 MJ ME/kg). In all studies, apparent sodium absorption rate increased with sodium intake, but sodium faecal output was not significantly affected by dietary sodium content or total sodium intake, suggesting nearly 100% absorption of ingested sodium.…”
Section: Sodium Balance and Dietary Requirementsmentioning
confidence: 99%